Acute pancreatitis in a patient with normal lipase: a case report: Akutni pankreatitis z normalnimi vrednostmi lipaze: prikaz primera - Kitanovski, Tjaša; Grahek, Andrej; Garvas, Žan (Acta Medico-Biotechnica, 2024)
This case report highlights the rare occurrence of acute pancreatitis in a patient exhibiting normal lipase levels. The patient presented to the emergency department with abdominal pain and fever. Laboratory tests indicated an acute inflammatory process but a negative lipase value. The diagnosis was established by a CT scan showing necrotizing pancreatic changes with elevated carbohydrate-deficient transferrin (CDT) levels, suggesting alcohol as the etiology. Management involved supportive care, aggressive fluid resuscitation, nutritional support, and empirical antibiotic therapy, which led to clinical improvement. This case emphasizes the importance of a comprehensive clinical assessment beyond standard biochemical markers in diagnosing and managing pancreatitis.